Building an entrepreneurial and sustainable society - Hernández-Sánchez, Brizeida R., 1970-; Sánchez-García, José C., 1957-; Moreira, António Carrizo (Practice, progress, and proficiency in sustainability (PPPS) book series., 2020)
"This book explores the field of entrepreneurship covering topics as sustainable entrepreneurial competences, exploration of new opportunities, sustainable intrapreneurship, and social and sustainable entrepreneurial ecosystems" --